The influence of metformin in the etiology of selected cancers - Pawałowska, Monika; Markowska, Anna (Contemporary Oncology/Współczesna Onkologia, 2012)
Obesity, hypertension and glucose tolerance disorders have become a growing concern in recent years. It is estimated that over 220 million people suffer from diabetes. It is a condition conducive to cardiovascular diseases, nephropathy, retinopathy and neuropathy but also to the development of many types of cancer. Insulin resistance and hyperinsulinemia lead to increased concentration of insulin-like growth factors, activation of IGF-R receptors, activation of PI3K and Ras-Raf pathways and result in increased cell division. The greatest risk is associated with developing stomach, pancreatic, colorectal, esophageal and lung cancer as well as breast and cervical cancer. Numerous cohort studies have confirmed that diabetic patients treated with metformin show a lower cancer morbidity and mortality rate. The dominant mechanism of action is activation of the AMP-activated protein kinase (AMPK) pathway and inhibition of mTOR protein, the key protein to regulate cell growth, apoptosis, proliferation and protein synthesis. Many clinical trials are currently under way to investigate the effectiveness of metformin in the prevention and treatment of neoplasms.